A Marginal Case of Secondary Opening In GƏˁƏZ. (2nd September 2020) - Butts, Aaron Michael
Abstract: In this article, I discuss a feature in the development of Gǝˁǝz that I term 'secondary opening' following the grammatical tradition of Masoretic Hebrew. By secondary opening, I refer to the development that produced a form such as bäḥär 'sea', which is prominent in EMML 6907 (twelfth cent.?), from *baḥr-, the typical realization of which is baḥr in Standard Gǝˁǝz. While admittedly marginal, forms with secondary opening are, I argue, nonetheless important since they provide a rare glimpse at a variety of Gǝˁǝz that was not the direct ancestor of what would eventually become Standard Gǝˁǝz.